1996
DOI: 10.1002/chin.199639028
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Absence of Platinum Enhancement of a Photoreaction on TiO2‐CO Photooxidation on Pt/TiO2(110).

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Photocatalysis has received remarkable interest as a green and sustainable solution for the energy and environmental issues since Fujishima and Honda’s first reports of UV-light-induced redox chemistry on TiO 2 . This consequently has intrigued the fundamental investigations of photochemistry of TiO 2 surface largely employing rutile TiO 2 (110) surface as the prototypical model surface. Insights have been recently achieved into the photochemistry of several important molecules involved in photocatalytic reactions, such as O 2 , CO, methanol/formaldehyde, H 2 O, and H adatoms …”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has received remarkable interest as a green and sustainable solution for the energy and environmental issues since Fujishima and Honda’s first reports of UV-light-induced redox chemistry on TiO 2 . This consequently has intrigued the fundamental investigations of photochemistry of TiO 2 surface largely employing rutile TiO 2 (110) surface as the prototypical model surface. Insights have been recently achieved into the photochemistry of several important molecules involved in photocatalytic reactions, such as O 2 , CO, methanol/formaldehyde, H 2 O, and H adatoms …”
Section: Introductionmentioning
confidence: 99%
“…The reactions between CO and O 2 have been studied in detail on metals, and it is a model system for studying the mechanisms of thermal oxidation and photooxidation on TiO 2 . Yates and co-workers investigated the photooxidation of CO on TiO 2 (110) at ∼100 K and found that UV irradiation led to either photodesorption of chemisorbed O 2 or photooxidation of CO to CO 2 . ,, The energy thresholds for both O 2 and CO 2 photon-stimulated desorption (PSD) were at ∼3.1 eV, corresponding to the band gap of TiO 2 . This threshold indicates that the photochemistry is initiated by the generation of electron−hole pairs in the substrate.…”
mentioning
confidence: 99%